Pendekatan Islam Pada Dokter Dalam Penanganan Kesehatan Mental Anak Akibat Pandemi Covid-19: Peran Dokter, Penanganan, anak, Kesehatan mental, Pandemi - Asih Dwi Cahyani asih (Kampurui Jurnal Kesehatan Masyarakat, 2022)
Research on the hypothesis during the period of the emergence of the Covid-19 Pandemic in 2020, which has now become a global crisis that not only threatens people's health physically, but also mentally. So much bad news has been received, making people anxious about the lives of themselves, their family, closest friends, and even the surrounding environment, which in turn can threaten the safety and mental health of the Indonesian population, especially the health of children who do not have good immunity such as people in the era. Lately, many children have experienced psychological mental disorders due to the potential for causing health problems from the Covid-19 pandemic; However, health services during the Covid-19 pandemic often face obstacles, including due to damaged or inadequate health facilities. The author's new problem in addressing the mental health experienced by children due to the current pandemic is not easy. This research aims to solve the problem so that children can continue to live in a healthier, more adaptive and productive mental state. This research was conducted in relation to the development of graphic media to increase flood disaster preparedness. The population in this study were children aged 6-8 years in the Martapura area of ​​South Kalimantan. This study uses the ADDIE model method (Analyze, Design, Development, Implementation, and Evaluation) with data collection techniques through interviews when carrying out doctors intership at Ratu Zalecha Martapura Hospital, South Kalimantan, observation, pretest and post-test. The conclusion obtained is that the use of graphic media is effectively used to increase children's immunity during a pandemic. The results of the analysis of this research show that the presence of the doctor's role is expected to be a savior in handling in order to reduce the feeling of anxiety in parents for children and adolescents with good mental health can achieve and maintain optimal psychological health, social and well-being functions amid the pandemic .